Novel compound heterozygous variants (c.971delA/c.542C > T) in SLC1A4 causes spastic tetraplegia, thin corpus callosum, and progressive microcephaly: a case report and mutational analysis - Mohamed, Feda E.; Ghattas, Mohammad A.; Almansoori, Taleb M.; Tabouni, Mohammed; Baydoun, Ibrahim; Kizhakkedath, Praseetha; John, Anne; Alblooshi, Hiba; Shaukat, Qudsia; Al-Jasmi, Fatma (Frontiers in Pediatrics, 2023)
Spastic tetraplegia, thin corpus callosum, and progressive microcephaly (SPATCCM) are linked to SLC1A4 genetic variants since the first reported case in 2015. SLC1A4 encodes for the neutral amino acid transporter ASCT1 that is involved in the transportation of serine between astrocytes and neurons. Although most of the reported cases are of Ashkenazi Jewish ancestry, SPATCCM has also been reported in Irish, Italian, Czech, Palestinian, and Pakistani ethnicities. Here in, we report two Pakistani male siblings from a non-consanguineous marriage presented with global developmental delay associated with spastic quadriplegia, microcephaly, and infantile spasm. Since infancy, both siblings suffered from seizure-acquired microcephaly with brain MRI demonstrating generalized atrophy of the frontal, temporal and parietal lobes with a prominence of the subarachnoid spaces, widening of the Sylvian fissures and enlargement of the ventricular system not compatible with the chronological age of both patients associated with thinning of the corpus callosum. Whole exome sequencing of both affected brothers revealed a novel compound heterozygous variants in the SLC1A4 gene (NM_003038) segregating from their parents. The maternal c.971delA (p.N324Tfs*29) deletion variant disturbs the transcript reading frame leading to the generation of a premature stop codon and its subsequent degradation by nonsense-mediated mRNA decay as detected through expression analysis. The paternal c.542C>T (p.S181F) missense variant was predicted deleterious via multiple in silico prediction tools as the amino acid substitution is speculated to affect the overall ASCT1 structural confirmation due to the loss of an H-bond at the core of the protein at this position which might affect its function as concluded from the simulation analysis. The presented cases expand the genetic and clinical spectrum of ASCT1 deficiency and support the importance of including SLC1A4 gene screening in infants with unexplained global neurodevelopmental delay regardless of ethnicity.